The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1142/s0217979210064319
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive and Photoconductive Features of the Nanostructured Materials

Abstract: Photoconductive and photorefractive characteristics of fullerene- and nanotubes-doped organic thin films based on conjugated organics, such as polyimide, polyaniline, pyridine, etc. have been studied. In addition, the liquid crystal mesophase with nanoobjects has been investigated. The increase of the charge carrier mobility of nanosensitized organics has been established. The nonlinear refraction and cubic nonlinearity have been investigated at wavelength of 532 nm via four-wave mixing technique using Raman-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…In the previous studies 5, 6,9 we have shown the formation of barrier-free charge transfer pathways, increased dipole moment, and increased specific (per unit volume) local polarizability in some organic matrices doped with fullerenes, carbon nanotubes and quantum dots, where the formation of intermolecular complexes predominated over the intramolecular donor-acceptor interaction. It is necessary to take into account that the charge transfer between matrix organic molecule donor fragment and nanasensitizers can be organized due to their high electron affinity energy (for example, electron affinity energy is close to 2 eV for shungites 10 , to 2.65 eV for fullerenes 5,8 and to 3.8-4.2 eV for quantum dots 11 ) that is more than the ones for intramolecular acceptor fragments (for example, electron affinity energy of COANP acceptor fragment is close to 0.54 eV 12 and to 1.14-1.4 eV for polyimide one 13 ).…”
Section: Organic Nanocomposites Studymentioning
confidence: 80%
See 1 more Smart Citation
“…In the previous studies 5, 6,9 we have shown the formation of barrier-free charge transfer pathways, increased dipole moment, and increased specific (per unit volume) local polarizability in some organic matrices doped with fullerenes, carbon nanotubes and quantum dots, where the formation of intermolecular complexes predominated over the intramolecular donor-acceptor interaction. It is necessary to take into account that the charge transfer between matrix organic molecule donor fragment and nanasensitizers can be organized due to their high electron affinity energy (for example, electron affinity energy is close to 2 eV for shungites 10 , to 2.65 eV for fullerenes 5,8 and to 3.8-4.2 eV for quantum dots 11 ) that is more than the ones for intramolecular acceptor fragments (for example, electron affinity energy of COANP acceptor fragment is close to 0.54 eV 12 and to 1.14-1.4 eV for polyimide one 13 ).…”
Section: Organic Nanocomposites Studymentioning
confidence: 80%
“…The obtained products can be considered as new materials for photonics application in a broad spectral range. This study permits to define also different areas of applications of these materials doped with nanoobjects [1][2][3][4][5][6] . It should be remarked that the main reason to use the fullerenes, shungites, and quantum dots is connected with their unique energy levels and high value of electron affinity energy.…”
Section: Introductionmentioning
confidence: 99%
“…[13]. They were, respectively: ∼ 10 It should be mentioned that nonlinear optical parameters of nanoobjects-doped structures are larger than those obtained for traditional nonlinear inorganic systems and for pure organics.…”
Section: Bulk Propertiesmentioning
confidence: 96%
“…The possible mechanism to increase the laser-induced change in the refractive index, nonlinear refractive index and cubic nonlinearity has been explained in the papers [8,9,[13][14][15]. The possible mechanism to increase the laser-induced change in the refractive index, nonlinear refractive index and cubic nonlinearity has been explained in the papers [8,9,[13][14][15].…”
Section: Photorefractive Features Of the Organic Materials With Carbomentioning
confidence: 99%
“…It is well known that promising nano-objects such as fullerenes, carbon nanotubes (CNTs), quantum dots (QDs), shungites, and graphenes are found to permit different areas of applications of these nano-objects [1][2][3][4][5][6][7][8][9]. The general view of some of the nano-objects indicated above is shown in Figure 7.1.…”
Section: Introductionmentioning
confidence: 99%